Conception of Logistics Management System for Smart Factory - Quan Chong, Zhen; Yee Low, Cheng; Mohammad, Ubaidullah; Abd Rahman, Ramhuzaini; Bahari Shaari, Mohd Saiful (International Journal of Engineering and Technology, 2018)
An interconnected, data driven smart logistics management system is crucial in a smart factory in context of Industry 4.0. Applying the concept of cyber-physical systems (CPSs) and Internet of Things (IoT) will create a standardized logistics system. This system can be applied across the supply chain to enable the sharing of information in real-time which consequently optimize logistics processes. In this project, a conceptual model of a smart logistics management system between a supplier and a manufacturer using NFC smart tags technology is developed and its application is shown using prototype demonstrator. The system is equipped with functions to monitor and manage logistic related data. The interface is built using windows form application and android phone application. The developed modelâ€™s abilities and specifications in context of industry 4.0 is evaluated using the VDMA Toolbox Industry 4.0. In the end this system achieved an average of level 4 in the Industry 4.0 evaluation and this system provides a concept on applying a smart logistic management system for manufacturers as a key step in transforming into smart factories.Â Â